‘The prehistory of Asian collections in Paris’: Ting Chang, Travel, Collecting, and Museums of Asian Art in Nineteenth-Century Paris, Aldershot: Ashgate 2013 - Partha Mitter (Journal of Art Historiography, 2014)
The work deals with three major collectors of Asian art in Paris in the 19th century. Enrico Cernuschi and Émile Guimet (founder of Musée Guimet) acquired their substantial collection through travelling abroad while Edmond Goncourt amassed his collection at home through dealers. As the author argues, the influential postcolonial critiques of museum collections as instruments of power and authority do not take into account labour and social relations, and somatic experiences of travels to Asia. Cross-cultural encounters between Europe and Asia led to subtle inversions of power, undermining European sense of superiority. Additionally, she throws light on extensive networks and complex political, commercial, monetary relations, especially bimetallism, as well as the material conditions that affect art collection.